Ovarian response to the human chorionic gonadotrophin stimulation test in normal ovulatory women: the impact of regressing corpus luteum - Järvelä, Ilkka Y; Niinimäki, Maarit; Martikainen, Hannu; Ruokonen, Aimo; Tapanainen, Juha S (Fertility and sterility, 2007)
To evaluate the impact of the regressing corpus luteum on the hormone secretion during hCG stimulation. The hCG stimulation test in the early follicular phase has been used to assess the capacity of the ovarian theca cells to secrete steroids. A prospective observational study. University hospital. The study group consisted of 11 women with confirmed ovulation in the past cycle (corpus luteum positive [CL+]) and the control group of 11 women using oral contraceptive pills (OC; no CL). An hCG test (5,000 IU IM) was performed 2 to 4 days after menstrual bleeding, and the ovarian response was measured at 0, 48, and 96 hours after injection. Changes in serum concentrations of P, 17-hydroxyprogesterone (17-OHP), androstenedione (A), T, E(2), and vascular endothelial growth factor (VEGF), and in ovarian vasculature and volume (three-dimensional power Doppler ultrasonography) were measured. Secretion of P and 17-OHP increased after hCG injection in the CL group, whereas no change was observed in women on OCs (P < or = .001). Concomitant increases were observed in volume and vasculature of the ovary with a CL (P<.05), but not in the contralateral ovary or in women on OCs. The changes in volume and vasculature correlated with levels of P and 17-OHP (P<.05). The regressing corpus luteum from the past menstrual cycle reactivates and secretes steroids in response to hCG stimulation performed during the early follicular phase, which should be taken into account when comparing hormone profiles of ovulatory and anovulatory women.